Konsep Uang dan Kebijakan Moneter dalam Ekonomi Islam - Hasallyt, Nena (EJESH: Journal of Islamic Economics and Social, 2024)
Monetary policy in Islamic economics is part of the branch of economics that discusses the nature, function and influence on economic activity in a country. Monetary policy can maintain economic stability, this can be seen by balancing the amount of money that is widely spread in a balanced way. If any money in circulation exceeds or is greater or less than a number of goods and services, then the economy in a country will be chaotic. The method of writing this article uses a qualitative research approach. The data analysis technique is in the form of descriptive analysis. Descriptive itself is a research result that is described as clearly as possible based on research